2003
DOI: 10.1002/adma.200305315
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Hollow Nickel Submicrometer Spheres

Abstract: tures of these systems may be ideal for biomedical applications in which one desires to deliver cells into the body for a therapeutic purpose (e.g., regeneration of tissues or organs). [25,26] Experimental Sodium alginate (M w = 300 000; Pronova Biopolymers, Norway) was dissolved in 2-(N-morpholino)ethanesulfonic acid (Sigma) buffer (pH 6.5, 0.3 M NaCl) at room temperature, and the peptide was added to the alginate in the presence of N-hydroxysulfosuccinimide (Pierce) and 1-ethyl-3-(dimethylaminopropyl) carbod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(124 citation statements)
references
References 28 publications
4
119
1
Order By: Relevance
“…In reduced saturation magnetization, ~ 24% [6] or ~ 38% [7] of the bulk value at 300 K. of the sample is about 0.12 at 50 K, and it goes down to about 0.02 at 380 K. This is much smaller than the theoretically analyzed value, i.e. 0.5, for a system of randomly oriented Stoner-Wohlfarth (SW) particles [14].…”
Section: Magnetic Measurements and Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…In reduced saturation magnetization, ~ 24% [6] or ~ 38% [7] of the bulk value at 300 K. of the sample is about 0.12 at 50 K, and it goes down to about 0.02 at 380 K. This is much smaller than the theoretically analyzed value, i.e. 0.5, for a system of randomly oriented Stoner-Wohlfarth (SW) particles [14].…”
Section: Magnetic Measurements and Analysismentioning
confidence: 79%
“…Two stable ground states, the single domain and the vortex curling, have been obtained in theory for this special structure. Experimentally, there are many works concerning the synthesis and magnetic properties of Ni or Co hollow spheres [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…12D) were prepared by reducing NiSO 4 with NaH 2 PO 2 in an emulsion system. 96 When this process is conducted under hydrothermal condition using Ni(DS) 2 (dodecylsulfate) as the precursor, 50-60 nm nickel hollow spheres were obtained.…”
mentioning
confidence: 99%
“…The exchange coupling effect among the Ni nanoparticles will be reduced due to the isolation effect of the nonmagnetic matter. Meanwhile, the sample exhibits an enhanced coercivity (ie: Hc) value (239 Oe) compared to that of bulk Ni (0.7 Oe) 23 or that of hollow nickel sub-micro spheres (32.3 Oe), 9 hollow Ni nanospheres (102 Oe) 10 and dandelion-like Ni nanostructures (130.3 Oe) 24 at room temperature. Earlier studies in the magnetic nanosystems have shown that the effective anisotropy reins the coercivity, 25,26 which might explain why dendrite Ni possesses much higher coercivity.…”
Section: Magnetismmentioning
confidence: 99%
“…Up to now, there are a variety of techniques used to produce Ni nanoparticles, such as chemical reduction, 4 hydrothermal reduction, 5,6 thermal decomposition of organometals, 7,8 emulsion technique 9,10 and so forth. Generally, most of those wet-chemical methods require the use of highly toxic organometals or reducing agents, which could bring in toxic gases or impurities or a high processes temperature etc., against the development trend of green chemistry and chemical processes.…”
Section: Introductionmentioning
confidence: 99%